Lexical stress in childhood apraxia of speech: acoustic and kinematic findings...2013 American Speech-Language-Hearing Association Convention in Chicago, Illinois and the 2014 Conference on Motor Speech in Sarasota, Florida. - Kopera, Hailey C.; Grigos, Maria I. (International Journal of Speech-Language Pathology, 2020)
Purpose: This study investigated the acoustic and articulatory movement parameters underlying lexical stress production in children with apraxia of speech (CAS), children with articulation/phonological delay (i.e. speech delay, SD), and children with typical speech-language development (TD). We examined whether there were group differences in these instrumental measures of stress production. Method: Participants were 24 children (seven CAS, eight SD, nine TD) between three and seven years of age. Acoustic and kinematic measures, including acoustic duration, peak and average fundamental frequency, and jaw movement duration and displacement, were taken from perceptually accurate productions of a strong-weak form. Relative stress analyses were conducted using the Pairwise Variability Index (PVI). Result: There was a significant difference between the CAS and TD groups in the PVI for movement duration, with the CAS group showing a smaller movement duration contrast between stressed and unstressed syllables. There were no significant group differences for displacement or any of the acoustic variables. Conclusion: The kinematic findings suggest reduced temporal control for lexical stress production in children with CAS. This finding surfaced during analyses of perceptually accurate productions but suggests a possible basis for lexical stress errors in CAS that could be explored in future studies.